Giant trees enhance zoochorous plant dispersal in sacred groves and human settlements of the Western Ghats, India - Omkar Pai; Jayant Sarnaik; Archana Godbole; Gunwant Mahajan; Akshay Gawade; Kevin Matteson (PLoS ONE, 2026)
In India and other countries, large and ancient trees that persist in sacred groves and human-dominated landscapes support ecosystem services, including frugivore-mediated seed dispersal. In this study, we assessed the ecological significance of ‘giant’ trees (>1 m trunk circumference) in Vanzole Village, Western Ghats, India. We documented 82 giant trees belonging to 20 species in four sacred groves and surrounding human settlements. Sacred groves harbored a higher species richness of large trees (14 species, N = 44) than human settlements (8 species, N = 38). Tree composition varied, with Mangifera indica (Mango) and Artocarpus heterophyllus (Jackfruit) dominating in human settlements, whereas Terminalia bellirica (Beheda) and several other species were more abundant in sacred groves. Giant trees in human settlements exhibited larger canopy diameter (p = 0.002) and DBH (p < 0.001), while trees in sacred groves were significantly taller (p < 0.001). Sapling recruitment was notably higher in sacred groves; Caryota urens saplings were found under 91% of trees in groves (mean = 56.0) versus 47% in settlements (mean = 4.9). The larger-seeded Strychnos nux-vomica was nearly absent in human settlements (5%) compared to sacred groves (77%). Our study highlights the unique conservation value of sacred groves due to their retention of numerous and diverse giant trees. Together with remnant large trees in human settlements, this network is vital for sustaining the regeneration of zoochorous species by supporting the activity of hornbills and other frugivores.